Advances and perspectives for antimicrobial peptide and combinatory therapies - C, Santos; G. R, Rodrigues; L. F, Lima; M.C.G, dos Reis; N.B, Cunha; S.C, Dias; O. L, Franco (Frontiers in Bioengineering and Biotechnology, 2022)
Antimicrobial peptides (AMPs) have shown cell membrane-directed mechanisms of action. This specificity can be effective against infectious agents, which acquired resistance to conventional drugs. The AMPs membrane-specificity and their great potential to combat resistant microbes have brought hope to the medical/therapeutic scenario. The high death rate worldwide by antimicrobial resistance (AMR), has busting the search for new molecules and product developments, mainly antibiotics. In the current scenario, other strategies including the association of two or more drugs, have contributed to the treatment of difficult-to-treat infectious diseases, above all, those caused by bacteria. In this context, the synergistic action of AMPs associated with current antibiotic therapy can bring essential results for producing new effective drugs to overcome AMR. This review presents the advances obtained, in the last five years, in the medical/antibiotic therapy scenario, with the use of products based on AMPs, as well as perspectives on the synergic effect of AMPs with current drugs for bacterial infectious disease treatment.